Связь между объемом и площадью для шаров в многообразиях Финслера–Адамара - Борисенко, А.А.; Олин, Е.А. (Видавничий дім "Академперіодика" НАН України, 2007)
We give upper and lower estimates for the ratio between the volume of a metric ball and the area of its surface in Finsler–Hadamard manifolds with pinched S-curvature. We apply these estimates to get the limit at infinity for this ratio. The derived estimates are a generalization of the well-known result in the Riemannian geometry.